Religion and power - Fuentes Belgrave, Laura (2024)
Volume 17.2 of Siwô’: Journal of Theology and Socio-Religious Studies, corresponding to July-December 2024, proposes an interdisciplinary reflection on the link between religion and the exercise of power from different areas and approaches that include; the study of a hagiographic theme to examine its polysemy of cognitive, cultural and epistemic meanings in the Costa Rican context, the analysis of the discussions on the relationship between body and power in the first conflicts of Pauline Christianity, the visibility of colonial violence and its consequences on religious education in the Chilean educational system, research on the participation of evangelical figures in Uruguayan politics in the 21st century, the study of experiences with spirituality in survivors of sexual exploitation in Bolivia, and the exploration of the notion of family as a central concept for Brazilian neoconservatism, in a superstructural dimension of the State that is related to neoliberalism, and arises as a reaction to the demands of the feminist and LGBTQIAP+ movements.